Methodological aspects of evaluation of state budge! programmes - Bivainis, Juozas; Butkevičius, Algirdas (Journal of Business Economics and Management, 2003)
The paper deals with the reasonability of allocation of public financial resources. It presents an integrated evaluation model applicable to budget programmes and capable of deepening the comprehensiveness as well as the objectivity of programme evaluation aimed at benchmarking. The nucleus of the model consists of four components: evaluation of relevance, evaluation of efficiency, evaluation of fitness, and the synthesis of the said evaluations. The contents and main methodological aspects of each component are described. First Published Online: 14 Oct 2010